System of Comparative and Global Law: from the global legal families to the new Common Law, (Journal of the Sociology and Theory of Religion, 2018)
Mr. Sánchez-Bayón PhD clarifies how there may be about two hundred State ordinances, divided between native civil systems (families of Common Law Anglo-Saxon, Continental or Civil Law, and mixed), plus derivative syncretic and hybrid (eg socialist, indigenous, Eastern), accompanied by religious systems (eg canon law, Jewish, Muslim, Protestant, Hindu), and a rich harmonizing regulation from international organizations (both universal, regional, sectoral, etc.). In short, the reading of this work enables the reader as a politico-legal operator of globalization, since it allows us to understand the complex system of current planning, to be able to act in a world where everything is interconnected in real time.